Social determinants of oral health in an indigenous community of Chile: preliminary data of a mixed qualitative and quantitative study - Cynthia Cantarutti; Gerardo Yévenes; Agueda Muñoz-del-Carpio-Toia; Daniela Adorno-Farias; Ricardo Fernández-Ramires; Alan Roger Santos-Silva; Jean Nunes dos Santos; Ignacio Molina-Ávila; Wilfredo Alejandro González-Arriagada (BMC Oral Health)
Abstract Introduction Certain aspects of indigenous communities, such as cultural practices and access to care, have been discussed as potential determinants of oral health. However, research on this topic remains limited. Understanding the factors influencing oral health and their perceptions is crucial for developing culturally appropriate interventions. This study aims to evaluate the determinants and self-perception of oral health through a mixed study within a specific indigenous community in the north of Chile. Furthermore, this is the first study to examine oral health in the Quechua and Aymara communities of Chile. Methods This exploratory study was conducted in in two phases: a quantitative phase, involving clinical examination and administration of questionnaires; and qualitative phase, consisting of interviews with subset of participants from the quantitative phase. A descriptive statistic of the quantitative data was performed. Results While no significant differences were found between indigenous and non-indigenous population in this city of Chile, differences were observed between the two main indigenous communities (Aymaras and Quechuas). Historical factors appeared to influence these differences. Belonging to the Aymara community emerges as a significant determinant of oral health, characterized by a greater need for oral rehabilitation, barriers to accessing dental care, lower self-perception of the quality of oral health. Educational level and rurality were identified as factors potentially affecting the oral health status of this community. Conclusion Ethnicity can influence in oral health, primarily in relation to rurality and educational level. This study found no significant overall differences in oral health between Indigenous and non-Indigenous participants. However, Quechuas exhibited better oral health than Aymaras. Participants demonstrated good oral health knowledge and a positive attitude towards prevention, despite recalling limited education in their youth. We emphasize the need for implementing strategies for oral health promotion and prevention that consider cultural, linguistic and specific needs of these communities.